Sistema de informação para gerenciamento de equipamentos médicos-hospitalares - Piccinini, Patricia Strapasson (2016)
The medical equipment, under sanitary vigilance rules, comprehend all equipment in use in the health field with medical, odontological, laboratorial or physiotherapeutic purpose, which are used either directly or indirectly for diagnosis, therapy, rehabilitation, or monitoring of human beings. The maintenance of these equipment is attributed to the clinical engineering area. The clinical engineering acts on development, management, maintenance and capacitation of medical-hospital equipment (MHE), within the hospital, aiming to contribute to the patients? quality of life. In order to improve the management of these equipment, it has allied with informatics, by means of information systems in the maintenance field. Most of the existing softwares for the hospital area are commercial, expensive and are meant to patients, beds and medical records managing. The existence of informatization systems with the aim of helping maintenance may cut down the time and the cost for this activity. The purpose of this study is to analyze and to implement an information system for managing the maintenance of MHE. This system is 100% Web, multiplatform, and uses a prioritizing method for preventive and corrective maintenance. Customized forms were created for each MHE, aiming the standardization of storage of solutions for each maintenance. For the developing of the system, the Object Oriented Analysis was applied, with techniques of software engineering. The system code was developed using PHP programming language, using a Bootstrap frontend framework and a PostgreSQL database. When the system was ready, software testing methods were created, providing itineraries to test the software?s usability. Comparing to SIGEMH and other softwares on the market, it was found that the majority regards the managing aspects of MHE, while SIGEMH aims the prioritization and standardization of forms relative to maintenance. Some functionalities present in other softwares were not developed, but new functionalities were implemented, such as: storage of technical rules and manuals for online searching, standardization of post-maintenance forms and the method which defines the order of equipment for service execution.